Assessing the Impact of Concurrent Tunnel Excavations on Rock Mass Deformation Around Existing Structures - Maoyi Liu; Qiang Ou; Xuanxuan Ren; Xuanming Ding (Applied Sciences)
Due to the complexity of planning and constructing underground lines, construction challenges—such as close proximity and multi-line interactions—are increasingly being recognized, along with their associated safety hazards. The visual observation of tunnel deformation and changes in the surrounding strata is difficult. In this study, laboratory model experiments were conducted using a mixture of liquid paraffin, n-tridecane, and silica gel powder, combined in specific proportions to create a transparent material that simulates natural soft rock. The new tunnel was designed to simultaneously cross over and under two existing tunnels. The impact of the new tunnel on the existing tunnels was examined, with excavation length and soil layer thickness considered as the primary influencing factors. The results indicate that excavating the new tunnel causes settlement deformation in the tunnels above and heave deformation in the tunnels below. The magnitude of deformation increases as excavation progresses but decreases with the greater thickness of the soil interlayer. For an existing tunnel, variations in the thickness of the soil interlayer not only affect its own deformation but also disturb the tunnel on the opposite side. Therefore, to ensure safer and orderly urban tunnel construction and to address the “black box” effect, it is essential to study the deformation characteristics of existing tunnels and their surrounding rock during the construction of new tunnels.